(untitled) (Revista de Investigaciones Universidad del Quindío, 2014)
The open source and open hardware systems are an economical, efficient and flexible tool to implement and develop technology in the classroom. These tools allows us the construction of complex systems by using hardware and software designed by others, providing great flexibility thanks to the availability of the code and schematic circuits, thus achieve adjust the behavior of some applications obtaining benefits: reduced development time, expanding applications, modularity and correcting problems in a practical way. Additionally, these systems are extremely useful for the case in which it is necessary to reduce costs, common in educational environments of our region with very limited resources. The quality of tools for application of development is very good and have nothing to envy to commercial equivalents. It also aims to engage students either related in projects to matter but also graduation projects in the culture of open Source both software and hardware . Particularly, the GIDET has been developing applications with PIC and ATMEL microcontrollers, robotics and other flat on the IDEA areas (Integrated Depeloment Enviroment for coding Algorithms) software graphical environment developed in the region, which allows the construction of programs based on algorithms designed in flowcharts and / or high-level languages (C, C + + ) with the IDEA in addition to designing the application at the end you can download the executable program in microcontroller-based systems. The systems that have made the open hardware applications use the same system connecting the arduino modules, allowing simultaneous connection of multiple cards for prototyping with some complexity. On the arduino based on design, they can be used with modules offered by other companies using the same technology. Modules are open architecture. In the IDEA may benefit both routines and hardware drawings required to build the application. From research and classroom applications are being developed with equally open hardware systems based on wireless technologies.